Re-intermediation of Malaysian traditional travel agencies using ICT and non-ICT strategies - Munikrishnan, Uma Thevi (2018)
The rapid technological innovation, large advertisement investments opportunities and the ability to consolidate the fragmented tourism products and services have enabled online travel agencies (OTAs) to be the leading global intermediaries replacing the role of SME traditional travel agencies. However, adopting ICT is one of the many strategies used by SME traditional travel agencies to circumvent disintermediation and to remain competitive and relevant in the industry. Malaysia still lags when it comes to ICT adoption, although it is perceived to increase the degree of survivability and competitiveness. As such, this paper identifies the ICT and non-ICT strategies embraced by Malaysian SME traditional travel agencies to to circumvent disintermediation and hence re-intermediate successfully in this digital era. Past literature have shown there is no one theory can explain the innovation adoption stages of an organisation. As such, this study integrates the Technology-Organisation- Environment framework (TOE) with DTI e-business adoption ladder’s classification of stages and Environment-management strategies (EMS) to investigate the ICT adoption pattern, drivers, inhibitors and non-ICT strategies embraced by traditional travel agencies as a re-intermediation strategies. The ICT adoption drivers and inhibitors are found to conform to TOE framework. Factors such as (i.e. perceived relative advantages, perceived trialability, compatability, IT infrastructure, IT skills/knowledge, owners’ attitude, organisational readiness, strategic orientation, high IT investments cost, perceived barriers, firm size, competitive pressure, trading partner pressure, external IS support and industry trend) are found to influence ICT adoption across the levels. Also, the non-ICT strategies embraced by the traditional the agencies do conform to EMS framework. Non-ICT strategies (i.e. competitive aggression, public relation, voluntary action, dependence development, smoothing, collaboration, partnership, alliances, domain selection and diversification) are found to influence ICT adoption. However, this study revealed the ICT adoption pattern did not conform to the DTI framework’s classification of stages but revealed a non-staged ICT adoption pattern. This study employs multiple case studies to ensure the issues are explored through multiple lenses. Semi-structured interviews, website content analysis, document analysis and direct observation are used to collect data from fourteen case firms located in Malaysia. A total of fourteen interviews were carried out with industry experts, hence, fourteen cases were constructed based on in-depth interviews with the CEO-owner who are the key decision makers in the organisation. Extant literature showed that a consistent and integrated framework for studying ICT adoption at various level was lacking. This study contributes to theory as it responds to the said claim by developing an integrated framework by incorporating elements from EMS and stage models along with TOE framework to provide a comprehensive understanding through new insights and go beyond one fixed theory. Its implication for managers and policy makers are twofold. Recognising the ICT and non-ICT factors at various level could assist the CEOs and policy makers to device specific strategies for business growth and sustainability.